Day 1 Wed, February 24, 2016 2016
DOI: 10.2118/179019-ms
|View full text |Cite
|
Sign up to set email alerts
|

Minimize Formation Damage in Water-Sensitive Unconventional Reservoirs by Using Energized Fracturing Fluid

Abstract: Slickwater has been widely used for hydraulic fracturing as it is inexpensive and able to carry proppants into the fracture. However, such fluid is unsuitable for water-sensitive formations, such as Montney. Water saturation around the fracture increases and clay swells when water leaks-off into matrix, both hindering natural gas flowing from matrix into fractures. N 2 or CO 2 energized water-based fracturing fluids have been widely used in water-sensitive formation as they can minimize fluid leak off during f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…In water-sensitive reservoirs possessing high clay contents, fracturing fluid containing a small amount of water and large gas volume is preferred in order to reduce formation damage caused by high capillary pressure and permeability discontinuity as the impacts of clay swelling [25]. Foam also can reduce the damage around wellbore due to invaded fluid which eventually reduces the water volume used for hydraulic fracturing.…”
Section: Hydraulic Fracturing Fluids For Shalesmentioning
confidence: 99%
“…In water-sensitive reservoirs possessing high clay contents, fracturing fluid containing a small amount of water and large gas volume is preferred in order to reduce formation damage caused by high capillary pressure and permeability discontinuity as the impacts of clay swelling [25]. Foam also can reduce the damage around wellbore due to invaded fluid which eventually reduces the water volume used for hydraulic fracturing.…”
Section: Hydraulic Fracturing Fluids For Shalesmentioning
confidence: 99%
“…The success of this operation depends on whether the fracturing fluid has satisfactory rheological properties and a suitable proppant carrying capacity . Many novel fracturing fluids, such as viscoelastic surfactants (VESs), slick water, supramolecular polymers, energized fluids, and supercritical carbon dioxide (CO 2 ), have been designed and developed through oilfield chemistry research. Nevertheless, traditional guar-based linear or cross-linked fracturing fluids are still the most commonly used fluids in oilfields due to their desirable performances and low costs. …”
Section: Introductionmentioning
confidence: 99%
“…Water-based fracturing fluid is the most commonly used fluid, such as guar gum fracturing fluid, slick-water fracturing fluid, clean fracturing fluid, and so on. , However, it is reported that usually only 5–50% of the injected fluid can be successfully returned to the ground. These retained fluids (or so-called filtration loss fluid, or invading fluid) often cause greater damage to the reservoir matrix permeability, such as water-sensitivity damage and water-locking damage. Water-sensitivity damage can be improved by adding clay stabilizer into the fracturing fluid, while well shut-ins after hydraulic fracturing and adding cleanup additives are effective for water-locking damage. The effectiveness of well shut-ins after fracturing depends on the reservoir physical properties. It has been also pointed out that well shut-ins may reduce the fracture/matrix connectivity, adversely affecting overall hydrocarbon production.…”
Section: Introductionmentioning
confidence: 99%